2019
DOI: 10.1016/j.scitotenv.2019.03.469
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mode of action of pollutants impairing the fish larvae escape response with the vibrational startle response assay

Abstract: The escape response evoked by vibrational stimuli and its habituation, essential behaviors for fish larvae survival, can be altered by neurotoxic environmental pollutants commonly found in our aquatic ecosystems.In this study we have analyzed the suitability of the Vibrational Startle Response Assay (VSRA) to obtain mechanistic information about the mode of action (MoA) of the chemicals impairing the escape response and its habituation. As a proof of concept, the pathophysiological mechanisms behind the action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…As it has been described in other target organisms (Faria et al, 2019a(Faria et al, , 2019b, D. magna responses to repetitive light stimuli are biphasic. The response to light stimuli increases until a maximum response is reached, and then the response decreases due to habituation (Bedrossiantz et al, 2020).…”
Section: Behavioral Assayssupporting
confidence: 56%
“…As it has been described in other target organisms (Faria et al, 2019a(Faria et al, , 2019b, D. magna responses to repetitive light stimuli are biphasic. The response to light stimuli increases until a maximum response is reached, and then the response decreases due to habituation (Bedrossiantz et al, 2020).…”
Section: Behavioral Assayssupporting
confidence: 56%
“…In this regard, it is important to address if fish larvae survival can be compromised by exposure to such pollutants at realistic concentrations and also address the possibility to use automated and easily implemented methods with highthroughput potential to test a broad array of known and unknown neurotoxic pollutants present in the aquatic ecosystems. Recently we developed and validated the Vibrational Startle Response Assay (VSRA), an automated in vivo assay for identifying chemicals impairing the escape response and its habituation in zebrafish larvae (Faria et al, 2019a;Faria et al, 2019b). The assay is based on measuring the distance moved by the larva during the startle responses evoked by repetitive vibrational stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gupta et al [25], in a seminal article on neuroanatomical mapping of the zebrafish brain, found that 6 dpf zebrafish larvae exposed to 50 M VPA during early development presented a loss of glutamatergic signal in part of the statoacoustic ganglion leading to a decreased acoustic startle responsiveness. Glutamate dysregulation is thought to be implicated in the changes of the startle response through NMDA and mGlu5 receptors [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%